Attitudes towards end-of-life decisions and the subjective concepts of consciousness: an empirical analysis. - Lorella Lotto (Public Library of Science (PLoS), 2012)
Background People have fought for their civil rights, primarily the right to live in dignity. At present, the development of technology in medicine and healthcare led to an apparent paradox: many people are fighting for the right to die. This study was aimed at testing whether different moral principles are associated with different attitudes towards end-of-life decisions for patients with a severe brain damage. Methodology We focused on the ethical decisions about withdrawing life-sustaining treatments in patients with severe brain damage. 202 undergraduate students at the University of Padova were given one description drawn from four profiles describing different pathological states: the permanent vegetative state, the minimally conscious state, the locked-in syndrome, and the terminal illness. Participants were asked to evaluate how dead or how alive the patient was, and how appropriate it was to satisfy the patient's desire. Principal findings We found that the moral principles in which people believe affect not only people's judgments concerning the appropriateness of the withdrawal of life support, but also the perception of the death status of patients with severe brain injury. In particular, we found that the supporters of the Free Choice (FC) principle perceived the death status of the patients with different pathologies differently: the more people believe in the FC, the more they perceived patients as dead in pathologies where conscious awareness is severely impaired. By contrast, participants who agree with the Sanctity of Life (SL) principle did not show differences across pathologies. Conclusions These results may shed light on the complex aspects of moral consensus for supporting or rejecting end-of-life decisions.